Preferences and their correlation between children and their parents' attitudes towards non-pharmacological behaviour guidance techniques - A cross-sectional study - S.V. S. G. Nirmala; S K Inthihas; Dhigvijay Aerpogu; C Rama Subbareddy; Sivakumar Nuvvula (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dental treatment for children requires the use of behaviour guidance techniques (BGTs), which are used in the dental office to make children cope with dental treatment. Aim: Evaluate how children and parents felt towards BGTs used in a dental office, by attitude meter and to correlate them. Materials and Method: Children (200) from 7-17 years and their parents were selected randomly to participate in the study. Each child and parent was asked to watch four video scenes of live BGTs, which include Tell Show Do (TSD), Modeling, Reward system, and Hand holding. A questionnaire collected demographic data, and their expressive attitudes were assessed using Line of favour (LOF) scale and Kruskal-Wallis Test. Results: Most preferred BGTs for Group I was modeling, Group II Reward, Group III Tell Show Do, and Group IV was Modeling, with a mean score of 5.95, 6.04, 5.57, and 5.78, respectively. Gender wise preferences, 32% of boys and 34% of girls preferred modeling in Group I, whereas, in Group II, 20% of boys and 21% of girls preferred reward, respectively. Chi-square test revealed that there is no significant difference between the groups and gender for the preference of BGTs in Group I (P=0.893) and Group II (P=0.592). There was no significant correlation between preferences of children and their parents. Conclusion: Modeling was the most preferred BGT for primary school children and parents of High school children. A reward was the most preferred BGT for high school children. TSD was the most preferred BGT for parents of primary school children.